DYNAMICAL STUDY OF THE FLOW ALONG A TWO-DIMENSIONAL CHANNELWITH A RIGHT ANGLED BEND - BRIMA, A.; ATMANI, R.; BENTERCIA, M.; ACHOUR, B. (Courrier du Savoir; Vol. 10 (2010): Courrier du Savoir)
A two-dimensional incompressible laminar flow passing through a constant width channel with a ninety-degree turn is investigated. Based on the flow separation and recirculation phenomena downstream of the inner corner , a model profile for the axial velocity component is chosen. Concerning the channel segments upstream and downstream of the previous corner, the insertion of the velocity profiles (incorporating a distortion profile function) in the Navier-Stocks equations and the use of the integral method lead to a linear differential equation for the previous function. Whereas, the corresponding previous differential equation is not linear in the corner region. The analytical and numerical solutions for the first and last equations respectively are obtained and the Reynolds number Re as well as recirculation bubble effects on the flow variables are presented for () 540 Re 100 ≤ ≤ ; the experimental range of flow visualisation and measurement ) L'écoulement incompressible, laminaire et bidimensionnel le long d'une conduite coudée à 90° a été étudié. En se basant sur le phénomène de séparation et de recirculation just après le coude, un modèle de profil de la composante de vitesse axiale est choisie. Concerant les deux parties en amant et en aval du coude, l'introduction du profile de vitesse (introduction du profil de la function de deformation) à l'interieur des équations de "Navier Stocks" et l'utilisation de la méthode intégrale menent à une équation différentielle linéaire dont l'inconnue est bien la fonction de déformation. Alors que, l'équation différentielle précédente est non linéaire au niveau du coude. Les solutions analytique et numérique respectivement pour la première et la dernière équation différentièlle sont obtenues. L'effet du nombre de Reynolds aussi bien de la bulle de recirculation sur les variables de l'écoulement est présenté pour 100 Re 540 ≤< (plage expérimentale de mesure et visualization).